Biomethanation of fruit processing industry waste-water through high-rate reactor - GITANJALI, J; MEKALA, L; AHMED, O RIYAZ; RAO, K BALAJI; KAMARAJ, S (The Indian Journal of Agricultural Sciences, 2015)
The present paper reports a study conducted at Tamil Nadu Agricultural University, aiming at developing a highrate reactor for treating the food processing waste-water. It was found that the waste-water had low strength biodegradability by conducting batch experiment with and without mixing cattle-dung in different volatile solid proportion and cattle-dung ratio. The BOD and COD of the waste-water were found to be 540 and 2000 mg/L respectively and pH of the processing waste-water was 1.37 that lies in the acidic range. In the batch studies conducted, the maximum gas production was recorded per kg of Total Solid Content and Net Volatile Solid Content added was observed in crushed and over ripen sample as 87.95, 91.51 L and 82.05, 84.24 L respectively. The minimum gas production per kg of total solid content and volatile solid content added was observed in waste-water sample as 2.22 and 2.42 L respectively for the digestion period of 21 days. The high-rate reactor for treating the food processing waste-water was installed at a reputed firm. The COD removal efficiency, TS removal efficiency and VS removal efficiency was found to be about 50, 36 and 29% respectively. The biogas generation potential is estimated to be 60 m3/day. The industry saved not only electric power of 96 kWh/day, but also the sludge was used as manure, thus the waste disposal was in an environmentally friendly approach.